7-Azaindole Derivatives as Potential Antibacterial Agents: Azaindole Derivatives as Antibacterial Agents (Biological Sciences - PJSIR, 2009)
Azaindole analogues, as antimicrobial agent, have shown significant response against a number of gram positive and gram negative bacteria. In the present work, synthesis of novel derivatives of 7- azaindole and their antibacterial and cytotoxic activities are reported.